Statistic and Probabilistic Variations with Precipitation Predictions of Jordan - Bataineh, Ahmad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This thesis deals with the analysis of monthly rainfall data gathered from 66 meteorological stations for the hydrologic years from October 1960 to September 2017 that are distributed irregularly in the Kingdom of Jordan. The area with the help of Thessien polygon is divided into twelve main districts, and the representative number of stations were detected. In order to study and analyze the rainfall (precipitation) data, the used sample size is 57. Four data quality tests Normality, Consistency, Homogeneity, and Stationary/Unit root and also the trend analysis test were studied based on parametric and non-parametric tests. The proper probability distribution function was found for each region, among the main four distributions the Normal, the log-Normal, the Gumble, and the Gamma. In order to predict the further yearly precipitation data for each meteorological district, three diverse widely used time series models were used; the Moving average (MA), the Holt-Winters, and nine different combinations of ARIMA. For this reason, the data of hydrologic years 1960-61 up to 2015-16 were used as a training period and the hydrologic year 2015-16 measured precipitation data was used for testing the trained data set where the best representative model was designated among the models which has the closest forecasted 2016-17 value to the measured (actual) rainfall value. Also the best model for each region was selected to predict the 10 consecutive upcoming hydrologic years from 2017-18 to 2026-27. Even for each region the rainfall within the months (from October to May) were studies statistically and their wetness or dryness periods and their overall trends were determined. Keywords: Rainfall, Time series models, Trends, Wet or dry spells.

ÖZ: Bu tez, hidrolojik yıl Ekim 1960 ile Eylül 2017 arasında Ürdün Kırallığında düzensiz bir şekilde dağılmış 66 meteoroloji istasyonundan toplanan yağış verilerinin analizinden oluşmaktadır. Bu alan Thessien polygon yöntemiyle oniki ana bölgeye bölünmüş ve her bölgeyi ifade edilen istasyonlarla belirlenmiştir. Yağış donelerini irdeleyip analiz yapabilmek için kullanılan örnek büyüklüğü 57’dir. Dört done kalite testi, Normality, Consistency, Homogeneity, ve Stationary/tek kök yanında trend analizi testi parametrik ve parametrik-olmayan testler yardımı ile çalışılmıştır. Her bölge için, önemli olasılık dağılımları olan Normal, log-Normal, Gumble, ve Gamma arasından en uygun olasılık dağılım fonksiyonu belirlenmiştir. Her bölgenin yıllık yağış miktarını ileriye dönük tahmin edebilmek için üç farklı çok yaygın zaman serisi modelleri olan Moving average (MA), Holt-Winters, ve dokuz farklı bileşenli ARIMA kullanılmıştır. Bu nedenle, hidrolojik yıllar 1960-61 ile 2015-16 arasındaki yağış doneleri, modeli tanıtma ve hidrolojik yıl 2015-16 ölçülmüş (gerçek) yağış donesinin üretilen değerleriyle karşılaştırılarak en yakın uyumu veren modeli belirleyip o bölge için seçilmiştir. Ayrıca seçilen bu model kullanılarak takip eden 10 yılın (hidrolojik yıl 2017-18 ile 2026-27) değerleri tahmin edilmiştir. Her bölge için ayrıca Ekim – Mayıs ayları ıstatıstiksel olarak çalışılmış ve ıslaklık veya kuruluk dönemleri ile genel eğilimleri belirlenmiştir. Anahtar Kelimeler: Yağış, Zaman serisi modelleri, Eğilimler, Islaklık veya kuruluk dönemleri.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2019. Supervisor: Assoc. Prof. Dr. Mustafa Ergil.
Keywords: Civil Engineering; Climate--Rainfall--Jordan; Rainfall; Time series models; Trends; Wet or dry spells